PENERAPAN RUKHSAH TERHADAP IBADAH SHALAT PADA MASA PANDEMI - Zainuddin, Zainuddin; Misbahuddin, Misbahuddin; Muhammad Shuhufi (Journal of Innovation Research and Knowledge, 2024)
Worship is the obligation of a Muslim who is obedient to the Creator. Carrying it out is an obligation for his people, and there is no reason whatsoever to abandon this obligation. These obligations include prayer, fasting, zakat, and the Hajj which are pillars or pillars of Islam that must be believed and implemented. Humans, especially Muslims, have no reason to abandon these obligatory acts of worship, because in Islam there is relief for carrying out these obligatory acts of worship. The relief in question is Rukhsah. Rukhsah can be carried out when someone is of age which is permitted according to the terms and conditions. In this discussion, Rukhsah was carried out because there was an outbreak or pandemic of Covid-19 that had hit the whole world, including Indonesia. Due to the pandemic, all activities that gather the masses have been canceled, including worship and carried out from their respective homes. Therefore, Rukhsah is widely implemented during the current pandemic to make it easier to carry out worship. This article is a literature review sourced from several references relevant to the topic discussed. Data collection techniques come from researching relevant reference sources in the form of journals, articles, websites, books and other scientific works. The analysis technique for this research is through collection, analysis and drawing conclusions.